2011
DOI: 10.1080/03643107.2011.614532
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Structures of Elder Abuse Reporting Systems

Abstract: The purpose of this study is to understand the evolution, structure, and processes of statewide administrative structures of elder abuse reporting and response systems. This inquiry examines the background of elder abuse reporting in the United States. Specifically, it reviews the philosophical foundations of the policies that undergird the mechanisms and administration of elder abuse reporting systems. The study also examines the available descriptive data on service-delivery models across states to further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As Teaster and colleagues (2006) identified, federal legislation allows states to have flexibility in how they approach elder abuse, which was seen in this study. Thus, social workers not only need to understand state laws about elder abuse, but the barriers and obstacles associated with these laws, including how abuse is defined as argued by Mukherjee (2011), mandatory versus permissive/voluntary reporting requirements, and the entity that is responsible for investigations. While the flexibility in elder abuse policy between the states can have its benefits and allows for autonomy in state governance, it has created challenges as there are not clear national practices in the prevention of elder abuse, as was seen in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Teaster and colleagues (2006) identified, federal legislation allows states to have flexibility in how they approach elder abuse, which was seen in this study. Thus, social workers not only need to understand state laws about elder abuse, but the barriers and obstacles associated with these laws, including how abuse is defined as argued by Mukherjee (2011), mandatory versus permissive/voluntary reporting requirements, and the entity that is responsible for investigations. While the flexibility in elder abuse policy between the states can have its benefits and allows for autonomy in state governance, it has created challenges as there are not clear national practices in the prevention of elder abuse, as was seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Schmeidel and colleagues (2012) found that the threshold to trigger an investigation was so high that vulnerable elders in the community were unprotected. Donovan and Regehr (2010) identified other challenges that social workers face when confronting potential elder abuse, including issues of competency, misinterpreting the actions of a highly cooperative caregiver, balancing policy issues that differ between elder abuse and child abuse and domestic violence, language and time factors, and as identified by Mukherjee (2011), a lack of consistent definitions of abuse among mandatory reporters.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In most states, Adult Protective Services and law enforcement agencies are notified. 23 Social work and geriatric care teams may be called for assistance, and a multidisciplinary approach applied. In preparation for the potential recognition of elder abuse in the ICU setting, barriers to identification and intervention must be determined.…”
Section: Intervention In the Abuse Of The Elderly Icu Patientmentioning
confidence: 99%
“…The National Center on Elder Abuse estimates that 1 -2 million cases of elder abuse, neglect, and exploitation occur every year in the USA, yet less than one in five cases is reported. Some estimates suggest that only 1 in 27 cases is reported (Mukherjee 2011).…”
Section: Elders As Victims Of Crimementioning
confidence: 99%